PERBANDINGAN KINERJA KEUANGAN TAMAN SATWA TARU JURUG DENGAN PT. PEMBANGUNAN JAYA ANCOL TBK - Charismata Agonizo; Kristiyana Dananti (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2020)
The tourism industry can be a foreign exchange earner in a country including Indonesia. Educational tourism such as a zoo among which must be considered and maintained because it is related animal life and its habitat. Then it needs to be taken into financial performance, because it concerns about the needs of feed, maintenance and cleanliness and their business sustainablelity. This research was conducted to determine the comparison of financial performance between Taman Satwa Taru Jurug which is a city government company with PT. Pembangunan Jaya Ancol Tbk, which has been listed on the Exchange Indonesian effect. Variables used to compare is liquidity ratios (CR and CAR), solvency ratios (DAR and DER), ratios profitability (ROA and ROE), activity ratio (TATO and ITO). This study uses non parametricfor 2 independent sampels, the Mann Whitney U Test. The results of this analysis, each ratio in the two companies showed a value of sig>0.05 which means there was no significant difference in financial performance between Jurug Wildlife Park and PT. Pembangunan Jaya Ancol Tbk.. Keywords :  comparison of financial performance, financial ratios, and  tourism industry